Acupotomy Contributes to Suppressing Subchondral Bone Resorption in KOA Rabbits by Regulating the OPG/RANKL Signaling Pathway. (26th April 2021) - Wang, Tong; Guo, Yan; Shi, Xiao-Wei; Gao, Yang; Zhang, Jia-Yi; Wang, Chun-Jiu; Yang, Xue; Shu, Qi; Chen, Xi-Lin; Fu, Xin-Yi; Xie, Wen-Shan; Zhang, Yi; et al.
Abstract : Subchondral bone lesions, as the crucial inducement for accelerating cartilage degeneration, have been considered as the initiating factor and the potential therapeutic target of knee osteoarthritis (KOA). Acupotomy, the biomechanical therapy guided by traditional Chinese meridians theory, alleviates cartilage deterioration by correcting abnormal mechanics. Whether this mechanical effect of acupotomy inhibits KOA subchondral bone lesions is indistinct. This study aimed to investigate the effects of acupotomy on inhibiting subchondral bone resorption and to define the possible mechanism in immobilization-induced KOA rabbits. After KOA modeling, 8 groups of rabbits (4w/6w acupotomy, 4w/6w electroacupuncture, 4w/6w model, and 4w/6w control groups) received the indicated intervention for 3 weeks. Histological and bone histomorphometry analyses revealed that acupotomy prevented both cartilage surface erosion and subchondral bone loss. Further, acupotomy suppressed osteoclast activity and enhanced osteoblast activity in KOA subchondral bone, showing a significantly decreased expression of tartrate-resistant acid phosphatase (TRAP), matrix metalloproteinases-9 (MMP-9), and cathepsin K (Ctsk) and a significantly increased expression of osteocalcin (OCN); this regulation may be mediated by blocking the decrease in osteoprotegerin (OPG) and the increase in NF-κ B receptor activated protein ligand (RANKL). These findings indicated that acupotomy inhibited osteoclast activity and promoted osteoblast activity to ameliorate hyperactive subchondral bone resorption and cartilage degeneration in immobilization-induced KOA rabbits, which may be mediated by the OPG/RANKL signaling pathway. Taken together, our results indicate that acupotomy may have therapeutic potential in KOA by restoring the balance between bone formation and bone resorption to attenuate subchondral bone lesions.